Collaborative technologies in new factory's certification process - Mohiuddin, A. K. M.; Wee Hock, Quik (Asian Network for Scientific Information, 2005)
The present study has demonstrated how collaborative technologies with the support from the fundamentals of Copy EXACTLY! (CE) methodology could be utilized to ramp-up manufacturing capacity within a shortest possible time. As a result of globalization the start-up teams that are geographically disperse are gathered to collaborate using shared critical information. It becomes more apparent and this model proves to be a forerunner in streamlining business process, reducing product time to market and developing sustainable competitive advantage.